Experimental investigation on minimizing degradation of solar energy generation for photovoltaic module by modified damping systems. (15th January 2023) - Bhore, Chaitanya V.; Andhare, Atul B.; Padole, Pramod M.; Loyte, Akshay; Sofia Vincent, J.; Devarajan, Yuvarajan; Vellaiyan, Suresh
Graphical abstract: Highlights: Mounting configuration significantly impacts the natural frequencies of the PV module. Appropriate selection of mounting arrangement lowers induced vibrations of PV. PV module finite element model is prepared and validated. Mounting configurations are determined from harmonic response analysis. Reducing the micro-cracks generation increases the life of the PV module. Abstract: With the rapid increase in solar energy generation, it is common to see solar photovoltaic modules mounted on structures subjected to dynamic loading. These dynamic loads induce vibration in solar photovoltaic modules, which generate cracks and micro-cracks. This deteriorates the solar photovoltaic modules' performance and life, effectively reducing solar energy generation. In this context, this paper deals with modal and harmonic response analysis of solar photovoltaic modules. The photovoltaic module's natural frequencies and mode shapes for ten different mounting configurations are determined using the composite plate Finite Element Model for three separate solar photovoltaic technologies. The finite element model is validated by comparing it with experimental and published results. Acceleration, velocity and displacement responses are determined in harmonic response analysis for base excitation and body acceleration inputs separately. Moreover, harmonic response analysis is performed, for which the amplitude and Frequency of induced vibrations are decided based on measured metro train vibrations levels in the vicinity of the metro rail. It is observed that mounted natural frequencies are considerably affected by the mounting configuration. A comparison of first mode natural frequency between the first and last mounting configurations shows a difference of 214.9%. Harmonic response analysis gives the resonant acceleration, velocity and displacement peak levels for all ten mounting configurations. Based on the least number of resonant peaks and lower value of response amplitudes, the best and worst mounting configurations are identified for all three solar photovoltaic technologies. This study provides a basis for selecting the best mounting arrangements to achieve the best solar energy conversion efficiency with minor degradation of the solar photovoltaic modules subjected to induced vibrations.